Technology-Assisted Speaking Practice: The Role of the Cake App in Improving Students’ Speaking Skills - Klemensia Lende; Hernina Dewi Lestari (Explorations in English Learning, 2025)
This Classroom Action Research (CAR) aimed to improve the speaking skills of seventh-grade students at SMP Negeri 1 Wewewa Selatan through the use of the Cake application as a digital learning medium. The research was carried out in two cycles, each consisting of planning, acting, observing, and reflecting, involving 33 students of Class VII B in the 2024/2025 academic year. Data were collected through speaking tests, classroom observations, interviews, and documentation. The success indicators were set at 75% improvement in classroom participation and 85% of students achieving the Minimum Mastery Criterion (KKM) of 75. The findings showed substantial improvement in students’ speaking abilities after using the Cake application. The pre-test average score was 56.51%, categorized as “low.” In Cycle I, the post-test average increased to 60.24%, although only 21.21% of students met the mastery criterion. In Cycle II, the post-test average rose significantly to 75.15%, with 75.15% of students successfully achieving mastery. Observation results revealed notable gains in classroom participation, engagement, and pronunciation, increasing from an average score of 2.18 in Cycle I to 4.55 and 4.70 in Cycle II. Interview results supported these findings, showing that students became more confident, motivated, and interested in participating in speaking activities when learning with the Cake application. Overall, the research concludes that the integration of the Cake application effectively enhances students’ pronunciation, fluency, vocabulary mastery, confidence, and participation, demonstrating that digital media can significantly strengthen English speaking skills in junior high school learners